O Tribunal de Segurança Nacional e a repressão aos comunistas e integralistas (1936-1938) - Neves, David Rodrigues Silva (2013)
The Court of National Security was created in September11, 1936. This court was able to judge the communists that uprising against Vargas Govern in 1935. After Estado Novo Dictatorship beginning in November 11, 1937 this court gained authority of an Military justice also judging offense contrary the popular economy, sabotage, specially on period the Second World War and others against the National Security Affairs. Beyond of communists court national security condemned the Integralistas that participated of putsch in 1938. This research analyzes this Court by two cases: Nestor Contreiras Rodrigues, Integralista, arrested in 1938 by keeping war weapons in at farm near Rezende in Rio de Janeiro state and José Monte Junior, indicted to make communist publicity in São Paulo. Both as been condemned to one year in prison existed between them a predominant factor. The communist were treated with more severity than the Integralistas. However, we should to understand that Court National of Security was tied the repression structure of that historical period. As judging as condemned these instrument coercion were very important to maintenance of order